2007
DOI: 10.1007/s10562-007-9132-7
|View full text |Cite
|
Sign up to set email alerts
|

Observation of bimodal polyethylene derived from TiO2-supported zirconocene/MAO catalyst during polymerization of ethylene and ethylene/1-hexene

Abstract: The bimodal polyethylene obtained from TiO 2 -supported zirconocene/MAO catalyst was observed during polymerization of ethylene and ethylene/1-hexene. By means of XPS, it revealed that TiO 2 consisted of Ti 3+ (BE = 462.6 eV) and Ti 4+ (BE = 464.9 eV). The dual catalytic sites were attributed to the presence of Ti 3+ and Ti 4+ in TiO 2 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…However, by a heterogeneous catalytic system, only one catalyst fixed on the certain support (filler) can generate dual active sites due to the heterogeneity of the support. As observed by our previous work [8] using micro-TiO2 as a support for zirconocene/MAO catalyst, it also found that this catalytic support can produce a bimodal MWD polymer. For further study in production of bimodal MWD polymer here, the TiO2 in nanometer scale (nano-TiO2) was used instead for gaining an advantage of nanotechnology to the resulting product, along with its modification by gallium (Ga) and zirconium (Zr), which have been proven previously as a good modifier in the catalytic system [9,10].…”
Section: Introductionsupporting
confidence: 79%
“…However, by a heterogeneous catalytic system, only one catalyst fixed on the certain support (filler) can generate dual active sites due to the heterogeneity of the support. As observed by our previous work [8] using micro-TiO2 as a support for zirconocene/MAO catalyst, it also found that this catalytic support can produce a bimodal MWD polymer. For further study in production of bimodal MWD polymer here, the TiO2 in nanometer scale (nano-TiO2) was used instead for gaining an advantage of nanotechnology to the resulting product, along with its modification by gallium (Ga) and zirconium (Zr), which have been proven previously as a good modifier in the catalytic system [9,10].…”
Section: Introductionsupporting
confidence: 79%
“…However, the homogeneous liquid phase reaction of metallocene is lack of morphology control. Therefore, the supported catalytic system (heterogeneous system), which can improve this problem, has been developed [1]. It has been reported that many inorganic supports such as SiO 2 , Al 2 O 3 and MgCl 2 have been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been perceived that active center distribution also has a strong effect on MWD of polymer. It means that the surface structure of MgCl 2 affects on MWD, which influences the physical and mechanical properties, and processability of polymer 2,14 . Up to this point, it can be said that the controlling of polymer properties can be done by the modification of MgCl 2 and the addition of hydrogen.…”
Section: Chapter I Introductionmentioning
confidence: 99%